The long-term effect of age at school entry on competencies in adulthood - Katja Görlitz; Merlin Penny; Marcus Tamm (Freie Universität Berlin, School of Business & Economics, 2019)
The previous literature has shown that children who enter school at a more advanced age outperform their younger classmates on competency tests taken between kindergarten and Grade 10. This study analyzes whether these effects of school starting age continue into adulthood. Based on data on math and language test scores for adults in Germany, the identification of the long-term causal effects exploits state and year variation in school entry regulations. The results show that there are no effects of school starting age (SSA) on competencies in math and text comprehension. However, the long-term SSA effect is sizable on receptive vocabulary.
urn:nbn:de:kobv:188-refubium-23894-1
Keywords: I21; J21; J31; 330; school starting age; education; cognitive competencies; instrumental variable estimates